2017
DOI: 10.5138/09750185.2164
|View full text |Cite
|
Sign up to set email alerts
|

<em>Glinus oppositifolius</em> (L.) Aug. DC.: A Repository of Medicinal Potentiality

Abstract: <p>Plants have been used in the treatment of human diseases since centuries. Due to their medicinal values, more than 80% of the modern world population still rely on plants as their primary source of medicines. Traditional plant-based medicines are widespread in Asian countries like the Indian subcontinent, Bangladesh, China, Japan, Pakistan, Indonesia, Myanmar, and in the continent of Africa. Nowadays, plant-derived medicines are gaining wider acceptance even in developed countries of the Western world… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
0
0
Order By: Relevance
“…The scientists worldwide are engaged in designing the targeted therapeutics that can specifically exterminate cancer cells without harming the normal and healthy cells. The natural products isolated from algae [16], angiosperms [17][18][19] and lichens [20,21] have been utilized as viable sources of medicines to treat many diseases including cancer and injuries. Though, some studies have shown anti-oxidative properties of Euglena sp.…”
Section: Introductionmentioning
confidence: 99%
“…The scientists worldwide are engaged in designing the targeted therapeutics that can specifically exterminate cancer cells without harming the normal and healthy cells. The natural products isolated from algae [16], angiosperms [17][18][19] and lichens [20,21] have been utilized as viable sources of medicines to treat many diseases including cancer and injuries. Though, some studies have shown anti-oxidative properties of Euglena sp.…”
Section: Introductionmentioning
confidence: 99%